Time-Resolved Laser Spectroscopy of Semiconductors - Physical Processes and Methods of Analysis - Brudevoll, T.; Storebo, A. K.; Skaaring, O.; Kirkemo, C. N.; Norum, O. C.; Olsen, O.; Breivik, M. (IntechOpen, 2011)
None